Prośba o śmierć - wołaniem o miłość. Wybrane zagadnienia związane z prośbą chorego o eutanazję - Kotecka, Agnieszka (Wydział Teologiczny, UAM, 2010)
Having analysed selected motives inducing the sick to ask for euthanasia it appears it is not only physical pain, limitations caused by the illness or the loss of dignity and sense of life that are the main factors evoking this dramatic reąuest. Among other reasons there is also solitude, rejection and lack of love from the loved ones. The request for euthanasia appears then as a call for the love and presence of another human being. It is a dramatic attempt to attract attention. Its real aim turns out to be not to end life but to receive help. The reąuest for euthanasia itself is a morally reprehensible act as it is an attempt to take one's own life which is a gift from God and it is only God who can decide about its ending. Euthanasia then is a contradiction as far as both the natural law and the law of God is concerned and ought to be treated as murder.
A Request for Death - A Call for Love. Selected Issues concening the Request of the Sick for Euthanasia
Keywords: Euthanasia; Request for euthanasia; Motives for euthanasia